Adult attention-deficit hyperactivity disorder symptoms and psychological distress, hazardous drinking, and problem gambling: A population-based study. (July 2021) - McDonald, André J.; Cook, Steven; Turner, Nigel E.; Ialomiteanu, Anca R.; Mann, Robert E.; Bondy, Susan J.; Roerecke, Michael; McCready, John; Millstone, Dov; Hamilton, Hayley A.; Elton-Marshall, Tara; Rehm, Jürgen; et al.
Highlights: Adult ADHD symptoms are strongly associated with psychological distress. ADHD symptoms not linked to drinking problems after adjusting for other variables. ADHD symptoms not associated with gambling problems before or after adjustment. One of the first studies to assess the role of brain injury in these relationships. Abstract: Recognition of ADHD in the adult population is relatively recent. Epidemiological research examining the mental health impact of ADHD in adulthood is thus limited. The objective of this study was to examine whether adult ADHD symptoms are associated with psychological distress, hazardous drinking, and problem gambling, after controlling for traumatic brain injury and sociodemographic characteristics. We analyzed data from a population-based survey administered in 2015 and 2016 to adults aged 18 years and over in Ontario, Canada (N = 3, 817). Logistic regression was used to construct unadjusted and multivariable models for each of the three focal relationships. In the unadjusted models, ADHD symptoms were significantly related to psychological distress (OR = 9.3; 95% CI:6.1, 14.0) and hazardous drinking (OR = 2.1; 95% CI: 1.3, 3.4), but not to problem gambling (OR = 1.5; 0.5, 4.3). After adjustment, ADHD symptoms were significantly related to psychological distress (OR = 7.1; 95% CI: 4.6, 11.1), but not hazardous drinking (OR = 1.4; 95% CI: 0.8, 2.5) or problem gambling (OR = 0.6; 95% CI: 0.2, 2.5). This study further highlights the importance of clinicians assessing for concomitant ADHD and psychological distress in adults.